The use of chitosan-coated biochar for the improvement of heavy metals-contaminated soil and healthy food products - Hamzah, Amir; Priyadarshini, Rossyda; Lestari, Sri Umi (Journal of Degraded and Mining Lands Management, 2025)
Soil health is a global concern related to food health issues, and the intensity of using agrochemicals contributes greatly to contamination by Pb (lead), Cd (cadmium), Cu (copper), Zn (zinc), and other heavy metals. Land contaminated with heavy metals is absorbed by plants and transferred to tissue, causing food to be unhealthy for consumption. Soil improvers such as biochar and chitosan have been widely used for improvement, but the use remains partial. In this context, granular coating technology is the right choice for overcoming soil problems. Chitosan-coated biochar technology is an effort to combine biochar and chitosan, which are made into granules and function as soil amendments. Therefore, this study aimed to obtain oil amendments that are effective in reducing heavy metals in soil. The target was for the soil to be healthy as well as produce healthy and safe food products. A completely randomized design was used with three replications. The production of granular chitosan biochar was then investigated on vegetable plants. Growth observations were carried out every week until the plants were about to be harvested, while soil and heavy metal analysis was conducted before and after planting. The observed data were analyzed using an Analysis of Variance (ANOVA) and Least Significant Difference (LSD) tests. The results showed that a chitosan-coated biochar dose of 20 t/ha increased plant growth in all observed parameters. The use of chitosan-coated biochar reduced Pb from 10.77 mg/kg to 6.73 mg/kg, Cd from 5.01 mg/kg to 2.56 mg/kg, and Cu from  71.22 mg/kg to 25.65 mg/kg.